2014
DOI: 10.5194/bg-11-2411-2014
|View full text |Cite
|
Sign up to set email alerts
|

Forest summer albedo is sensitive to species and thinning: how should we account for this in Earth system models?

Abstract: Abstract. Although forest management is one of the instruments proposed to mitigate climate change, the relationship between forest management and canopy albedo has been ignored so far by climate models. Here we develop an approach that could be implemented in Earth system models. A stand-level forest gap model is combined with a canopy radiation transfer model and satellite-derived model parameters to quantify the effects of forest thinning on summertime canopy albedo. This approach reveals which parameter ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 70 publications
2
52
1
1
Order By: Relevance
“…, , Otto et al. ) specifically for this purpose. Although a few studies have used similar methods to examine temperate forests (Thompson et al.…”
Section: Introductionmentioning
confidence: 99%
“…, , Otto et al. ) specifically for this purpose. Although a few studies have used similar methods to examine temperate forests (Thompson et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, high eff s relative to the intermediate site indicated that the xeric site was using the remaining energy available to the site more efficiently. These results demonstrate that sites with higher biodiversity are better adapted to changes in resource availability by way of how they alter their reflective properties, such that energy partitioning is optimized (i.e., high absorption of solar radiation) and high entropy production can be maintained 5 (Gunawardena et al, 2017;Otto et al, 2014;Taha et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Forests store almost 50 % of the terrestrial organic carbon and 90 % of vegetation biomass (Dixon et al, 1994;Pan et al, 2011). Globally, 70 % of the forest is managed and the importance of management is still increasing both in relative and absolute terms.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed description and evaluation of the new multi-layer energy budget and multi-level radiative transfer scheme is given by Ryder et al (2014), Chen et al (2015) and McGrath et al (2015b). A new forest management reconstruction, which is needed to drive forest management in ORCHIDEE-CAN, is presented in McGrath et al (2015a), and the interactions between forest management and the new albedo scheme have been discussed by Otto et al (2014).…”
Section: Introductionmentioning
confidence: 99%